Інформація як об’єкт національної безпекової політики України - Венглінський, О. О.; Venhlinskyi, O. O. (Аналітично-порівняльне правознавство. - 2024. - № 3. - С. 42-47, 2024)
Надано аналіз системних характеристик інформації як об’єкта національної безпекової політики України в умовах сучасних викликів та загроз, пов’язаних з інформаційною агресією росії. Звертається увага на пріоритетне значення інформації серед об’єктів національної політики безпеки України. Доводиться, що інформаційна свобода вимагає пильного державного контролю та включення інформації до переліку об’єктів національної безпекової політики.

Attention is drawn to the priority value of information among the objects of the national security policy of Ukraine. It is argued that information freedom requires careful state control and inclusion of information in the list of objects of national security policy. Information threats to state security are considered as a combination of conditions and factors that pose a danger to the vital interests of the state, society, and individuals through negative informational influence on the consciousness and behavior of citizens, as well as destructive impact on information resources and informationtechnical infrastructure. Two types of information attacks are distinguished based on the object of influence: 1) purely technical information attacks aimed at the functioning of the technical equipment of information systems; 2) influencing people’s consciousness through the transmission of targeted information. Three main goals of information warfare are outlined: control of the information space and ensuring the protection of one’s information from enemy actions; using control over the information space to conduct information attacks on the opponent; increasing the overall effectiveness of armed information functions. It is argued that in order to prevent the above-mentioned negative consequences, the following measures should be taken at the State level: 1) development of a system of continuous monitoring and analysis of information flows for timely detection of potential threats and response to them; 2) introduction of information literacy programmes among citizens to reduce vulnerability to manipulative information and fake news; 3) cooperation with international partners and exchange of experience in the field of information security to increase the effectiveness of measures and improve strategies to counter threats. These steps can ensure a high level of information security that will contribute to stability, security and protection of national interests.

Представлен анализ системных характеристик информации как объекта национальной политики безопасности в условиях современных вызовов и угроз, связанных с информационной агрессией России. Обращается на приоритетное значение информации среди объектов национальной политики безопасности Украины. Доказывается, что информационная свобода требует тщательного государственного контроля и включения информации в перечень объектов национальной политики безопасности.
Information as an object of Ukraine’s national security policy
Keywords: інформація; інформаційна конкуренція; інформаційна інфраструктура; інформаційна війна; інформаційний захист; безпекова політика; кібербезпека; information; information competition; information infrastructure; information war; information protection; security policy; cybersecurity; информация; информационная конкуренция; информационная инфраструктура; информационная война; информационная защита; политика безопасности; кибербезопасность